Dataset of the complete mitogenomes of the mushroom corals FungiidaeNCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBINCBI - Liwei Li; Zhangwang Lu; Zhiwei Liu; Cheng Liang; Jun Wang; Yan Wang (Data in Brief, 2025)
Twenty-four mitogenomes of the mushroom corals (Fungiidae), representing 18 species from 12 genera, were sequenced and annotated. These mitogenomes exhibit high similarity, each containing the same 13 protein-coding genes (PCGs) and two rRNA genes as other scleractinian corals. Compared to the genes, the intergenic regions (IGRs) are more diverse. Interestingly, minisatellite sequences were identified in the IGRs between COX1 and trnM (IGRCOX1-trnM) and between ND4 and rrnS (IGRND4-rrnS) of most Fungiidae mitogenomes. Primarily due to the existence of minisatellites in IGRCOX1-trnM, the length of Fungiidae mitogenomes varies from 16,292 to 17,399 bp. Similar to the phylogenetic tree based on partial COI sequences, Bayesian phylogenetic trees constructed using 13 PCGs, IGRCOX1-trnM and IGRND4-rrnS divide Fungiidae into four distinct clades. However, the latter three trees provide a higher resolution of genus- and species-level evolutionary relationships. This mitogenome dataset will be valuable for better understanding the phylogeny of Fungiidae. The diverse IGRs in these mitogenomes may serve as a useful resource for developing Fungiidae DNA barcodes, while the identified minisatellites can facilitate studies on the population biology of Fungiidae.